Development of aircraft electric starter-generator system based-on active rectification technology - Bozhko, Serhiy; Yang, Tao; Le Peuvedic, Jean-Marc; Arumugam, Puvaneswaran; Degano, Marco; La Rocca, Antonino; Xu, Zeyuan; Rashed, Mohamed; Fernando, Weerahannadige; Hill, Christopher Ian; Eastwick, Carol; Pickering, Stephen J.; et al. (Institute of Electrical and Electronics Engineers, 2018)
More-electric aircraft (MEA) has become a dominant trend for modern aircraft. On-board MEA, many functions, which are conventionally driven by pneumatic and hydraulic power, are replaced with electrical subsystems. Starting aircraft engines with an electrical motor instead of using pneumatic power from the auxiliary power unit (APU) is one of the major characteristics of future aircraft. This paper presents the development of a novel electric starter-generator system for aircraft applications. The paper describes the main achievements of the project within the key areas including electric machines, power electronic converters, thermal management and overall system control design. The developed prototype has been tested successfully and the test results are presented in this paper.